Ex 1.3, 2 - Chapter 1 Class 12 Relation and Functions
Last updated at April 16, 2024 by Teachoo
Inverse of a function
Ex 1.3, 2 Deleted for CBSE Board 2025 Exams You are here
Ex 1.3, 3 (i) Important Deleted for CBSE Board 2025 Exams
Ex 1.3, 3 (ii) Deleted for CBSE Board 2025 Exams
Ex 1.3 , 4 Deleted for CBSE Board 2025 Exams
Ex 1.3, 5 (i) Deleted for CBSE Board 2025 Exams
Ex 1.3, 5 (ii) Important Deleted for CBSE Board 2025 Exams
Ex 1.3, 5 (iii) Important Deleted for CBSE Board 2025 Exams
Ex 1.3 , 6 Deleted for CBSE Board 2025 Exams
Ex 1.3 , 7 Deleted for CBSE Board 2025 Exams
Ex 1.3 , 8 Important Deleted for CBSE Board 2025 Exams
Ex 1.3 , 9 Important Deleted for CBSE Board 2025 Exams
Ex 1.3, 10 Important Deleted for CBSE Board 2025 Exams
Ex 1.3, 11 Deleted for CBSE Board 2025 Exams
Ex 1.3, 12 Deleted for CBSE Board 2025 Exams
Ex 1.3, 13 (MCQ) Important Deleted for CBSE Board 2025 Exams
Ex 1.3, 14 (MCQ) Important Deleted for CBSE Board 2025 Exams
Inverse of a function
Last updated at April 16, 2024 by Teachoo
Ex 1.3, 2 (Introduction) Let f, g and h be functions from R to R. Show that (f + g)oh = foh + goh (f.g)oh = (foh).(goh) Let f(x) = x, g(x) = sin x , h(x) = log x We will show (f + g) oh = foh + goh Let f(x) = x, g(x) = sin x , h(x) = log x To prove: We will show (f .g) oh = foh . goh (f .g) oh = foh . goh Ex 1.3, 2 Let f, g and h be functions from R to R. Show that (f + g)oh = foh + goh & (f.g) oh = (foh).(goh) Proving (f + g) oh = foh + goh L.H.S (f + g)oh = (f + g) (h(x)) = f (h(x)) + g (h(x)) = foh + goh = R.H.S Hence, (f + g) oh = foh + goh Proving (f .g) oh = foh . goh L.H.S (f . g)oh = (f . g) (h(x)) = f (h(x)) . g (h(x)) = foh . goh = R.H.S Hence, (f . g) oh = (foh) . (goh)